Compound Danshen Yeast 1.0 - Rongsheng Li; Jie Wang; Yuanyuan Han; Zhubo Dai (Science of Traditional Chinese Medicine)
Abstract. Background. Heterologous synthesis presents a promising new approach for accessing the active ingredients of traditional Chinese medicine (TCM), contributing to the conservation of natural medicinal resources. Compound Danshen preparation, a widely used TCM formulation, is designed to treat coronary heart disease and angina pectoris. It is primarily composed of Salviae Miltiorrhizae Radix et Rhizoma (Danshen), Notoginseng Radix et Rhizoma (Sanqi), and borneol (Bingpian). Danshen primarily yields tanshinones and phenolic acids, while Sanqi produces notoginsenosides. Borneol serves as an auxiliary agent to promote mental clarity, dissipate heat, and relieve pain. Objectives. The objective is to employ heterologous synthesis in a single yeast strain to produce the active ingredients of Compound Danshen preparation, and these include notoginsenosides, tanshinones, and borneol. Methods. Firstly, the “plug-and-play” terpene synthase screening framework in Saccharomyces cerevisiae was used for the identification of a novel, highly efficient bornyl diphosphate synthase. Furthermore, by leveraging the Compound Danshen preparation as a basis to concurrently reconstruct the biosynthetic pathways for the notoginsenoside precursor protopanaxadiol (a triterpene), the tanshinone precursor miltiradiene (a diterpene), and borneol (a monoterpene) within a single yeast strain. Results. This engineered strain, termed Compound Danshen Yeast 1.0, successfully produced protopanaxadiol at 62.34 mg/L, miltiradiene at 15.38 mg/L, and borneol at 2.54 mg/L in shake-flask fermentation. Conclusions. This research signifies the inaugural cross-species and multicomponent synthetic biology endeavor that enables the synthesis of active ingredients in engineered cells, setting the stage for the industrial manufacture of TCM compounds.